Meta-analysis of the prognostic value of CpG island methylator phenotype in gastric cancer. Issue 2 (17th January 2018) - Powell, A G M T; Soul, S; Christian, A; Lewis, W G
Abstract: Background: CpG island methylator phenotype (CIMP) has been identified as a distinct molecular subtype of gastric cancer, yet associations with survival are conflicting. A meta-analysis was performed to estimate the prognostic significance of CIMP. Methods: Embase, MEDLINE, PubMed, PubMed Central and Cochrane databases were searched systematically for studies related to the association between CIMP and survival in patients undergoing potentially curative resection for gastric cancer. Results: A total of 918 patients from ten studies were included, and the median proportion of tumours with CIMP-high (CIMP-H) status was 40·9 (range 4·8–63) per cent. Gene panels for assessing CIMP status varied between the studies. Pooled analysis suggested that specimens exhibiting CIMP-H were associated with poorer 5-year survival (odds ratio (OR) for death 1·48, 95 per cent c.i. 1·10 to 1·99; P = 0·009). Significant heterogeneity was observed between studies ( I 2 = 88 per cent, P < 0·001). Subgroup analysis according to whether studies showed a tendency towards poor (5 studies) or improved (5) outcomes for patients with CIMP-H tumours, revealed that CIMP-H was associated with both poor (OR for death 8·15, 4·65 to 14·28, P < 0·001; heterogeneity I 2 = 52 per cent, P = 0·08) and improved (OR 0·42, 0·27 to 0·65; P < 0·001, heterogeneity I 2 = 0 per cent, P = 0·960) survival. Conclusion: There was heterogeneity in the gene panels used to identify CIMP, which may explain the survival differences. Abstract : Heterogeneity in gene panels used